Untangling Small Arms and Transnational Organized Crime: Evidence from Abu Sayyaf in the Philippines 2014-2017 - I Wayan Raditya Wikantara; Bintang Corvi Diphda; Naghita Puteri Fashihah; Delphinia Gabrielle Svetlana Abel; Andrew Elnathan; Refa Defanda Witanto (Pena Wimaya, 2026)
This article examines Abu Sayyaf’s small arms and light weapons (SALW)-related activities in the southern Philippines during 2014-2017 through Phil Williams and Roy Godson’s Transnational Organized Crime (TOC) anticipation model. Existing studies have widely discussed Abu Sayyaf in relation to terrorism, maritime violence, kidnapping for ransom, and jihadist transformation, yet less attention has been given to analyzing the group through an integrated TOC framework. This study asks how the TOC anticipation model can explain Abu Sayyaf’s persistence during this period. Using a qualitative single case study design, the article relies on desk review and thematic analysis of academic works, policy reports, legal documents, and security studies. The findings show that Abu Sayyaf’s activities were sustained by the interaction of three dimensions. First, the economic model explains the role of illicit arms access, ransom-based financing, and maritime opportunity. Second, the political model highlights weak state capacity, porous borders, regulatory weakness, and local patronage networks. Third, the risk management model shows how Abu Sayyaf adapted through mobility, dispersal, and decentralized networks. The article concludes that Abu Sayyaf is best understood as a transnational organized criminal actor sustained by enabling conditions and adaptive operational practices.